The Role of Accounting in a Society: Only a techn(olog)ical solution for the problem of economic measurement or also a tool of social ideology? - Horvat, Robert; Korošec, Bojana (Naše gospodarstvo/Our economy, 2015)
The contribution juxtaposes the traditional neutralistic view on the role of accounting in a society as an activity of independent and unbiased measurement and presentation of real economic phenomena with the extended view on accounting as a socio-political practice and ideology. It also shows how the latter view impacts the understanding of the role of accounting and its reactions in light of the recent global financial crisis.
Keywords: accounting; auditing; social practice